Evaluation of Maize Grain Yield in Drought-Prone Environment of Southern Guinea Savanna of Nigeria - Takim, Felix O.; Olaoye, Gbadabo; Abayomi, Yakeem; Olakojo, Samuel; Isah, Matthew; Bankole, Foluso; Ishaq, Mohammed; Abdulmaliq, Suleiman (Journal of Agricultural Sciences (Belgrade), 2017)
Multi-location trials data obtained between 2007 and 2014 involving open pollinated (OPVs) and hybrid maize (Zea mays L.) were analyzed using the genotype and genotype x environment (GGE) and additive main effect and multiplicative interaction (AMMI) models to assess their performance and suitability as cultivars, identify promising genotypes and sites for further evaluations in the different locations of the southern Guinea savanna of Nigeria. The experiments were set up as a randomized complete block design with three replications in all the locations. The plot size consisted of two rows, 5m long with inter and intra row spacing of 0.75m x 0.4m for the early maturing varieties and 0.75m x 0.5m for Intermediate/Late maturing and hybrids. Two seeds were planted/hill to give a plant population of approximately 66,000 plants/ha (early) 54,000 plants/ha (intermediate/late). Data were collected on agronomic and yield parameters. The environment accounted for 84.80% and 90.42% of the total variation in grain yield of OPVs and hybrids, respectively. TZE-Y-DT STR C4 (early OPV) and white-DT-STR-SYN (intermediate/late OPV), TZE-W-Pop-DT STR-C5 (early maturing hybrids) and TZEEI 3 x TZEEI 46 (extra early genotype) were the most stable and good grain yields. The core test locations for evaluation of early OPVs, intermediate/late OPVs and hybrids are Ilorin/Ballah, Ejiba/Mokwa and Kishi/Badeggi, respectively. This study recommends that fewer but better locations that provide relevant information should be used for conducting multi-location trials and TZE-Y-DT STR C4, white-DT-STR-SYN, TZE-W-POP-DT STR-C5 and TZEEI 3 x TZEEI 46 should be further evaluated on farmer’s fields.